2004
DOI: 10.1016/j.jcf.2004.04.008
|View full text |Cite
|
Sign up to set email alerts
|

High heterogeneity of CFTR mutations and unexpected low incidence of cystic fibrosis in the Mediterranean France

Abstract: In this report, we present updated spectrum and frequency of mutations of the CFTR gene that are responsible for cystic fibrosis (CF) in Languedoc-Roussillon (L-R), the southwestern part of France. A total of 75 different mutations were identified by DGGE in 215 families, accounting for 97.6% of CF genes and generating 88 different mutational genotypes. The frequency of p.F508del was 60.23% in L-R versus 67.18% in the whole country and only five other mutations (p.G542X, p.N1303K, p.R334W, c.1717-1G>A, c.711+1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
2
20
1
1
Order By: Relevance
“…The geographical distribution of the p.F508del shows a decreasing frequency from the Northwest to the Southeast of Europe [13,24,29,31,33,34]. The Islamic Republic of Iran is located to the Southeast of Turkey, and based on this gradient, the observed lower frequency of the p.F508del is in agreement with this observation.…”
Section: Discussionsupporting
confidence: 83%
“…The geographical distribution of the p.F508del shows a decreasing frequency from the Northwest to the Southeast of Europe [13,24,29,31,33,34]. The Islamic Republic of Iran is located to the Southeast of Turkey, and based on this gradient, the observed lower frequency of the p.F508del is in agreement with this observation.…”
Section: Discussionsupporting
confidence: 83%
“…8 In heterogeneous populations, the number of different mutations is very large. [9][10][11][12] A worldwide survey found that 28 493 of the 43 077 studied CF chromosomes (66%) carried the p.F508del mutation. 13 The frequency of the p.F508del mutation differs between populations, ranging from 26% in Algeria and Venezuela to 47% in one Brazilian study and 87% in Denmark; other mutations also vary widely depending on the ethnic composition of the studied groups.…”
Section: Introductionmentioning
confidence: 99%
“…The E1104X mutation was later described in Germany by Reiss in 1993 (21), in France (4,23,24), and in US (10).…”
Section: Resultsmentioning
confidence: 99%